Perceived Inclusion of Islamic Finance: The Effects of Attitudes, Experience, Literacy, Religiosity, and Social Influences - Moh’d Khamis, Fauz; Isa, Mohamad Yazid; Yusuff, Noraini (Online Academic Press, 2024)
The existing literature lacks demand-side perception studies on Islamic finance and its determinants, especially in developing markets. This study examines the influences of attitudes towards Islamic finance (ATTIF), financial experience (FE), Islamic financial literacy (IFL), religiosity (RL), and social influences (SI) on the perceived inclusiveness of Islamic finance (PIIF). This study used purposive sampling to obtain 400 questionnaire respondents from Zanzibar, Tanzania. The Smart-PLS (4) was used for analysing the data. We discovered mixed perceptions among the respondents regarding the inclusiveness of Islamic finance. Furthermore, the findings revealed a positive and significant influence of ATTIF, FE, SI, and RL on PIIF. ATTIF mediates the effects of RL and SI. The effect of ATTIF on PIIF is mitigated by IFL. The two most significant factors that determine PIIF are SI and ATTIF. RL was high among respondents but less important in determining PIIF. Islamic financial institutions should design products that fit society’s needs by considering socio-cultural and economic dynamics. These findings have important policy implications for improving the inclusiveness of Islamic financial markets. This study provides new insight into the inclusion of Islamic finance and its determinants